Leaching effectiveness of desalinization by rainfall combined with wheat straw mulching on heavy saline soil. Issue 7 (7th June 2018) - Cui, Shiyou; Zhang, Jiaojiao; Sun, Mingfa; Chen, Huatao; Feng, Zhixiang
ABSTRACT: Natural desalting in saline land with shallow groundwater and high evaporation is proceeding slowly. The main objective of the study was to evaluate the efficiency of straw mulching on desalinization by rainfall in saline land. Two sites of Solonchaks with different electrical conductivity (EC1:5 ) were selected to compare topsoil (0–40 cm) EC1:5 dynamics between bare land and straw mulching treatment. Soil samples were taken from May 2014 to April 2015 for determination of EC and pH, initial and termination samples were also used to measure Na +, Ca 2+ and Mg 2+ for calculating sodium adsorption ratio. The results demonstrated that supplementing salt leaching with straw mulch significantly decreased the EC1:5 of the soil profile (0–80 cm) when compared with no mulch. The both of topsoil (0–40 cm) EC1:5 and EC a / EC i decreased exponentially with the increase of cumulative rainfall and D w / D s under straw mulching, respectively. 178.6 and 351.9 mm of averaging rainfall were needed for removing 80% of salts in the 0–20 and 0–40 cm soil profile layers, respectively across all the cases of straw mulching and various EC1:5 . These findings suggested that rainfall combined with straw mulching could be popularized as effective measures to ameliorate saline soil for agriculture and forestry utilization.